29.9k views
5 votes
Using f(x) = 5x + 4 and g(x) = x - 3,find: 1. f(g(6)) 2. g(f(-7)) 3. f(f(8)) 4. g(f(x))

1 Answer

3 votes

Answer:

Part 1):


  • f(g(6))=19

Part 2):


  • g(f(-7))=-34

Part 3):


  • f(f(8))=224

Part 4):


  • g(f(x))=5x+1

Explanation:

Considering the function


f(x) = 5x + 4


g(x) = x - 3

Part 1)

To evaluate
f(g(6)), you must find
g(6)

so


g(x) = x - 3

Put x = 6


g(6) = 6 - 3


g(6) = 3

Then


f(g(6))=f(3)


=5(3)+4


=19

Therefore,
f(g(6))=19

Part 2)

To evaluate
g(f(-7)), you must find
f(-7)

so


f(x) = 5x + 4

Put x = -7


f(-7) = 5(-7) + 4


=-35+4


=-31

Then


g(f(-7))=g(-31)


= (-31) - 3


=-34

Therefore,
g(f(-7))=-34

Part 3)

To evaluate
f(f(8)), you must find
f(8)


f(x) = 5x + 4

Put x = 8


f(8)=5(8)+4=40+4=44

Then


f(f(8))=f(44)=5(44)+4=220+4=224

Therefore,


f(f(8))=224

Part 4)

Evaluate


g(f(x))

As


f(x) = 5x + 4


g(x) = x - 3

so


g(f(x))=g(5x+4)


=(5x+4)-3


=5x+4-3


=5x+1

Therefore,


g(f(x))=5x+1

User Karol Kulesza
by
4.9k points